The Romantic Turn in Bible Translation (translation. a transdisciplinary journal, 2022)
The paper presents an overview of the history of Bible translation in the " Romantic" tradition of Buber and Rosenzweig. The tradition has its roots in the Romantic turn in cranslation of early nineteenth-century Germany, hut three other forces also shaped the translation ideas and pract ices of this tradition: general linguistic ideologies of the ni neteenth century; the philosophical climate of the l nterbellum period in Germany; and the hermeneutic a nd exegetical heritage of the rabbinic tradition.